2020
DOI: 10.1186/s41182-020-00225-8
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in nutritional status of children who lived in temporary shelters in Bhaktapur municipality after the 2015 Nepal earthquake

Abstract: Background The nutritional status of children may deteriorate after natural disasters such as earthquakes. A 7.8 Richter scale earthquake struck Nepal in 2015 that affected 1.1 million children. Children whose homes were destroyed and had to live in temporary shelters were at risk of malnutrition. With the support of Nagasaki University School of Tropical Medicine and Global Health (TMGH) and Siddhi Memorial Hospital (SMH), we conducted a nutritional survey of under-5 children living in temporary shelters in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Communicable diseases Multiple studies conducted worldwide have shown that disaster adversely affects child growth (Mahapatra et al 2000;Hoddinott and Kinsey 2001;Portner 2010;Dhoubhadel et al 2020). Large-scale emergencies in high-, middle-, and low-income countries have increased morbidity and mortality of infants and young children.…”
Section: Child Nutrition and Physical And Mental Well-being In Disastermentioning
confidence: 99%
See 2 more Smart Citations
“…Communicable diseases Multiple studies conducted worldwide have shown that disaster adversely affects child growth (Mahapatra et al 2000;Hoddinott and Kinsey 2001;Portner 2010;Dhoubhadel et al 2020). Large-scale emergencies in high-, middle-, and low-income countries have increased morbidity and mortality of infants and young children.…”
Section: Child Nutrition and Physical And Mental Well-being In Disastermentioning
confidence: 99%
“…Portner (2010) pointed out that each disaster occurrence increased the prevalence of stunting among children. The bulk of food aid takes the form of grains, which mainly contain carbohydrates (Webb et al 2017;Dhoubhadel et al 2020). A study conducted after the 2011 Great East Japan Earthquake (GEJE) by Inoue et al (2014) showed that most food aid received, such as rice balls or bread, was carbohydrate-based, possibly because of their ready provision and abundance in emergency food pantries.…”
Section: Macro-nutrient and Micro-nutrient Deficienciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Noncommunicable diseases can also be provoked by emergency situations where low availability of health food and lack access of medical care (WHO, 2020). Based on a previous study during post earthquake in Nepal, the prevalence of underweight, stunting, and wasting increased (Dhoubhadel et al, 2020). Another study in post earthquake situation revealed that the food consumed were mostly have low nutritional value (Herrera-Fontana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors would like to add affiliation 2 into Bhim Gopal Dhoubhadel’s affiliations: Bhim Gopal Dhoubhadel 1,2. In addition, the full address of the affiliation 2 is changed as below.…”
mentioning
confidence: 99%